AKTIFITAS ANTIBAKTERI DARI SEDIAAN FOOTSANITIZER SPRAY KOMBINASI EKSTRAK BIJI KOPI (Coffea) DAN RIMPANG JAHE (Zingiber officinale) - Wilda Amananti; Dairoh Dairoh (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Foot deodorizing products currently circulating include anti-bacterial soaps, foot soaking powders, anti-prespirants, creams, and foot odor powders. However, these preparations have not been sold freely in Indonesia. In terms of use, it is considered impractical, because they have to use water when used. The product is considered ineffective, so there is a need for an innovation to remove foot odor that is healthy, more practical, and effective, namely Footsanitizer Spray. However, Footsanitizer Spray preparations in the market contain 70-95% alcohol. Excessive use of alcohol and chemicals can have health effects and irritant effects on the skin. Coffee has properties that are known to get rid of bad odors. Ginger rhizome (Zingiber officinale Roscoe) has been known to have antibacterial activity because it contains phenols, flavonoids, terpenoids, and essential oils. So that the combination of coffee bean extract and ginger rhizome is taken into consideration in making Footsanitizer Spray. Footsanitizer Spray in this study was made into 3 formulas. The difference in the formula is based on the comparison of the concentration of coffee bean extract and ginger root. Formula 1 with 25%: 45% coffee bean and ginger extract. Formula 2 with a ratio of 35%: 35% coffee bean extract and ginger rhizome. Formula 3 with a ratio of 45%: 25% coffee bean extract and ginger root. Based on the results of organoleptic testing and homogeneity, all formulas have a light brown color liquid with a distinctive aromatic smell. And soft taste. All formulas also produce homogeneous preparations. The results of the specific gravity test of the three formulas have not much different density. Namely, formula 1, formula 2 and formula 3 respectively are 1.064 gr / ml, 1.065 gr / ml, and 1.062 gr / ml. while the viscosity values ​​were 1.56 cp, 1.6 cp, and 1.61 cp, respectively. Formula 2 with a concentration of 35%: 35% has better antibacterial activity than other formulas. And it is included in the moderate barrier response category.